El Indígeno and High-Altitude Human Occupation in the Southern Andes, Mendoza (Argentina). Issue 1 (March 2016) - Neme, Gustavo
Abstract : The site El Indígeno contains the greatest known concentration of hunter-gatherer residential features in the southern Andes. Located at 3, 300 m asl in a meadow in the Cordillera of west-central Argentina, the site is notable for its 133 habitation structures, that—when considered along with the other characteristics of the site—represent an anomalous but perhaps not entirely unexpected adaptation to the highest altitude environment in the region. Based on radiocarbon dating and artifact typologies, the site was occupied between ca. 800 and 1500 B.P. It consequently represents the latest step in the indigenous colonization of what is arguably the most marginal environment in the region. This chronology suggests that the site was occupied when nearby lowland regions were under their most intensive use and during a time when new resources were incorporated into the high-altitude hunter-gatherer diet. In this article I report on research conducted at El Indigeno and compare the results of these studies to the regional record, ultimately concluding that regional population increase affiliated with the spread of increasingly complex socioeconomic systems most parsimoniously explains the intensive occupation of this large, high-altitude hunter-gatherer site.